Pemeriksaan Kesehatan Gratis sebagai Upaya Deteksi Dini Penyakit Tidak Menular di Komunitas - Asna, Alfi Fairuz; Trimulyono, Andi; Kurrohman, Faik; Adietya, Berlian Arswendo; Hanyfah, Dewinta Roebiyana; Farhana, Annisa; Syafrillia, Dewi; Safitri, Laela; Weslee, Chalvin; Alviskarahma, Keizha (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Non-communicable diseases (NCDs) are the most significant global public health challenge, significantly impacting both developed and developing countries. The results of the 2023 Indonesian Health Survey (SKI) indicate that NCDs such as diabetes mellitus, heart disease, and hypertension remain a major issue in Indonesia and Central Java Province.  Early detection of NCD risks through blood sugar, blood pressure, uric acid, and cholesterol level tests plays a crucial role in preventing and managing these chronic conditions. Objective: This community service activity aims to support NCD prevention efforts at the local level, particularly in Central Java, by involving the community in early detection programmes and promoting healthy behaviours. Method: This community service activity was carried out in June 2025 in Geneng Village, Demak, using a participatory method involving active community engagement. The program consisted of planning, health examinations, health education, and follow-up. A total of 51 participants from the productive and elderly age groups underwent health checks including blood pressure, blood glucose, uric acid, and cholesterol using standardized tools. The results were recorded, interpreted according to the Ministry of Health categories, and delivered to participants along with education on healthy lifestyles, such as dietary modifications, physical activity, and routine health monitoring. Data were analyzed descriptively and the results were also submitted to the local Public Health Center as input for non-communicable disease prevention programs. Result: The screening showed that 57.7% of respondents had high blood pressure, 13.04% had high blood sugar, 53.5% had high cholesterol, and 13.9% had high uric acid. These four types of screening can serve as important indicators and play a strategic role in the early detection of Non-Communicable Diseases (NCDs), enabling health interventions to be implemented in a timely and appropriate manner to prevent further complications. Respondents were then provided with an explanation of their screening results, including an interpretation of the health check results and recommendations for a healthy lifestyle. Conclusion: The conclusion from this community service activity is that some respondents still have hypertension, abnormal blood sugar levels, high uric acid, and high cholesterol.